The Sickle Cell Disease Ontology: recent development and expansion of the universal sickle cell knowledge representation. (1st April 2022) - Mazandu, Gaston K; Hotchkiss, Jade; Nembaware, Victoria; Wonkam, Ambroise; Mulder, Nicola
Abstract: The Sickle Cell Disease (SCD) Ontology (SCDO, https://scdontology.h3abionet.org/ ) provides a comprehensive knowledge base of SCD management, systems and standardized human and machine-readable resources that unambiguously describe terminology and concepts about SCD for researchers, patients and clinicians. The SCDO was launched in 2016 and is continuously updated in quantity, as well as in quality, to effectively support the curation of SCD research, patient databasing and clinical informatics applications. SCD knowledge from the scientific literature is used to update existing SCDO terms and create new terms where necessary. Here, we report major updates to the SCDO, from December 2019 until April 2021, for promoting interoperability and facilitating SCD data harmonization, sharing and integration across different studies and for retrospective multi-site research collaborations. SCDO developers continue to collaborate with the SCD community, clinicians and researchers to improve specific ontology areas and expand standardized descriptions to conditions influencing SCD phenotypic expressions and clinical manifestations of the sickling process, e.g. thalassemias. Database URL : https://scdontology.h3abionet.org/